Significance of monoclonal antibody SC3A expression in gastric carcinoma and precancerous lesion - Wu, Ji-Feng (World J Gastroenterol, 1997)
AIM: To study the significance of monoclonal antibody SC3A expression in gastric carcinoma and precancerous lesions. METHODS: Immunohistochemical staining and mucin histochemical staining were performed on paraffin-embedded sections from gastric benign and malignant lesions from 101 patients. RESULTS: SC3A positive rate was 80.3% (57/71) in lesions of gastric carcinoma. The expression of SC3A was not related to the classification, differentiation, metastasis and or survival rates. The positive rate of SC3A in cancers secreting acid mucin (90.2%) or sulphomucin (91.3%) was higher than that in cancers without acid mucin (20.0%) or sulphomucin (60.0%) (P < 0.01). The positive rate of sulphomucin was higher in cases of intestinal metaplasia with cancer (88.9%) than that of cases of intestinal metaplasia with a benign lesion (35.3%) (P < 0.01). Additionally, the positive rate of SC3A with sulphomucin in intestinal metaplasia (60.9%) was higher than that without sulphomucin (31.3%) (P < 0.05). CONCLUSION: SC3A monoclonal antibody might be helpful in the diagnosis of gastric cancer and the discernment of histogenesis.